The Path Dependence of European Copyright. - Larsson, Stefan (Scripted, 2011)
This article analyses the path dependence of European copyright. It shows how copyright is legally constructed, is harmonised through international treaties and European regulatory efforts in terms of InfoSoc Directive and the IPRED, and is also affected by the Data Retention Directive and the Telecommunications Reform package. Furthermore, the “secretly” negotiated ACTA agreement is discussed as it may impose stronger copyright on Member States. This means that the formulations and metaphors of how copyright is constructed and conceptualised contribute towards various lock-in effects as the dependence on the given path increases. The strong path dependence of European copyright law results in regulation that suffers from legitimacy issues. Copyright construction is a legal complex that in general is based on ideas of the conditions of an analogue world for distribution and production of copies, but it is armed with increasingly protective measures when faced with human conduct in the context of digital networks. To some extent, this most probably involves the expansion of the concepts and metaphors that once described only non-digital practice. The trend in European copyright is therefore strongly protectionist, through the expanding and strengthening of rights and their enforcement, and in that it is self-reinforcing, being locked into certain standards. The path dependence of European copyright serves as a strong argument for those who benefit from its preservation, signalling that there are power structures supporting the colonisation by this specific legal path of other legal paths that protect other values, such as consumer privacy or versions of integrity. There is a clear tendency in targeting the ISPs and other intermediaries in attempts to keep the copyright path intact. The development of European copyright, in its broad sense, not only re-builds the Internet in terms of traceability, but also law enforcement in terms of mass-surveillance. The digitalisation of society requires that new questions be asked as to how legal enforcement is or can be performed with regard to the mass-surveillance of the multitude of habits and secrets in our everyday lives. This means that there is a growing political responsibility for balancing privacy concerns and new and extreme possibilities for recording behaviour by means of data logs and digital supervision, all of which is part of the enforcement of copyright as a result of its strong path dependence. Thus, the path dependence of copyright leads to an imbalance of principal importance between the interests at stake. The imbalance lies in that a special interest is allowed to modify methods of legal enforcement from the reactive and particular to the pre-emptive and general. The special copyright interest gains at the expense of the privacy of everyone.
Keywords: lock-in effects; surveillance; Data retention; InfoSoc; ACTA; IPRED; Path dependence; copyright; law; enforcement; EU law